Kebertahanan Ikatan Sosial Masyarakat dalam Tradisi Mayah ketekan di Banjar Lawak, Desa Belok/Sidan - Dewi Gayatri, Ni Putu Ratna; Sudiarna, I Gusti Putu; Kaler, I Ketut (Humanis; Vol 26 No 3 (2022), 2022)
This study is aimed to recognize the meaning and the process of mayah ketekan tradition and to discover the implication of this tradition to the social boundary within the society of Banjar Lawak. The method applied in this study is the ethnographical method which is involved in qualitative method. The method of collecting data conducted in this study includes the following techniques, observation, interview, and literature review. This study has discovered that the tradition of mayah ketekan still carries meaningful values for the society of Banjar Lawak in depth; thus, this tradition is still conducted  although it has changed in some aspects within the tradition. In addition, the implication of the mayah ketekan tradition involves the strengthened  social boundary within the society of Banjar Lawak in the occasion of piodalan purnama kapat, when the tradition of mayah ketekan is conducted.